Mandatory lockdown impairs performance in professional soccer players. [El confinamiento obligatorio afectó al rendimiento de jugadores de fútbol profesional.] - Iván Peña-González; Alejandro Javaloyes; Fidel Agulló; Manuel Sempere; Aitor Soler; Manuel Moya-Ramón (Ramón Cantó Alcaraz, 2022)
COVID-19 caused a total halt in sport competition during 2020. The purpose of this study was to analyze the changes between pre- and post-lockdown competitive periods in the players' workload variables in competition. Seventeen professional football players were monitored using a WIMU PRO® inertial device throughout the 2019-20 season. Anthropometric and physical fitness were assessed with the aim to relate possible associations between these characteristics and the workload changes in the pre- and post-lockdown periods. During the lockdown, players carried out an 8-week guided self-training. There was a general decrement in the players' physical workload demands in competition, and the parameters related to high-intensity actions as accelerations and decelerations (-8.96% [ES: 0.64] and -11.04% [ES: 0.77] respectively; p < .05), Ind HSR (-35.57% [ES: 0.92]; p = .002), HMLD (-8.58% [ES: 0.66]; p = .016), PLOAD (-7.03% [ES: 0.54]; p = .047) and Vmax (-3.80% [ES: 0.65]; p = .016) can be highlighted. The results showed high negative correlations between match workload variables prior to the lockdown and the percentage of change in these variables after the lockdown period. Individual percentages of change showed high variability in players' changes. Individual self-training programs should be reviewed to minimize the impact of a "detraining" period in players' physical performance during possible new lockdown periods.